1999
DOI: 10.1007/s005850050826
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of thick, non-planar boundaries using the discontinuity analyser

Abstract: The advent of missions comprised of phased arrays of spacecraft, with separation distances ranging down to at least mesoscales, provides the scienti®c community with an opportunity to accurately analyse the spatial and temporal dependencies of structures in space plasmas. Exploitation of the multi-point data sets, giving vastly more information than in previous missions, thereby allows unique study of their small-scale physics. It remains an outstanding problem, however, to understand in what way comparative i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
12
0

Year Published

2001
2001
2010
2010

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 7 publications
(12 citation statements)
references
References 4 publications
0
12
0
Order By: Relevance
“…There are several methods for the analysis of boundaries between different fields and plasma populations using multispacecraft data (Dunlop and Woodward, 1999;Harvey, 2000;Haaland et al, 2004). Dunlop and Woodward (1999) make use of four-point magnetic field minimum variance analysis vectors to obtain a description of non-planar, accelerating boundaries.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…There are several methods for the analysis of boundaries between different fields and plasma populations using multispacecraft data (Dunlop and Woodward, 1999;Harvey, 2000;Haaland et al, 2004). Dunlop and Woodward (1999) make use of four-point magnetic field minimum variance analysis vectors to obtain a description of non-planar, accelerating boundaries.…”
Section: Methodsmentioning
confidence: 99%
“…Dunlop and Woodward (1999) make use of four-point magnetic field minimum variance analysis vectors to obtain a description of non-planar, accelerating boundaries. The local normal vector of the boundary can be calculated at each point, and the variation of this normal through space and with time can be assessed.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…These new instruments are, for example, the curlometer and the discontinuity analyzer (e.g. Dunlop et al, 1988Dunlop et al, , 1997Dunlop et al, , 1999 as well as the wave telescope (e.g. Musmann et al, 1974;Neubauer and Glassmeier, 1990;Lefeuvre, 1991, 1992;Stein et al, 1993;, 1996Pinçon and Motschmann, 1998), which has its roots in array signal analysis techniques developed for the interpretation of seismic array data (e.g.…”
Section: Introductionmentioning
confidence: 99%
“…play an important role in case of C2, affecting the results of the MVAB technique when applied on the central interval. We mention here that Dunlop and Woodward (1999), when studying, with synthetic data, how the local normal direction of a non-planar, ideal discontinuity, can be obtained by employing the planar MVAB method, showed that the errors are smaller when points from a short interval around the center of the structure are used. However, in case of a real event, a situation similar to that encountered by C2 on 24 June 2003 may occur.…”
Section: The Normal Magnetic Field Component On 24 June 2003mentioning
confidence: 91%